Multiplex and visual detection of African Swine Fever Virus (ASFV) based on Hive-Chip and direct loop-mediated isothermal amplification - Zhu, Yuan-Shou (Anal Chim Acta, 2020)
African swine fever is caused by African swine fever virus (ASFV), and has a mortality rate approaching 100%. It has already caused tremendous economy lost around the world. Without effective vaccine, rapid and accurate on-site detection plays an indispensable role in controlling outbreaks. Herein, by combining Hive-Chip and direct loop-mediated isothermal amplification (LAMP), we establish a multiplex and visual detection platform. LAMP primers targeting five ASFV genes (B646L, B962L, C717R, D1133L, and G1340L) were designed and pre-fixed in Hive-Chip. On-chip LAMP showed the limits of detection (LOD) of ASFV synthetic DNAs and mock samples are 30 and 50 copies per microliter, respectively, and there is no cross-reaction among the target genes. The overall performance of our platform is comparable to that of the commercial kits. From sample preparation to results readout, the entire process takes less than 70 min. Multiplex detection of real samples of ASFV and other swine viruses further demonstrates the high sensitivity and specificity of Hive-Chip. Overall, our platform provides a promising option for on-site, fast and accurate detection of ASFV.